Valores y actitudes del personal de enfermería que se aplican en los pacientes hospitalizados en el servicio de cirugía del hospital provincial general docente Riobamba y su influencia en el estado de ánimo de los pacientes durante el periodo marzo-septiembre 2011 - Huilcapi Chauca, Piedad Janeth (2011)
The study is citizen participation in health action, has the general objective: To determine the influence of the application of values and attitudes of nurses in the state of mind of the users who remain hospitalized in the Provincial Hospital of Surgery General Teaching Riobamba, research is descriptive research used a documentary.